Prevalence and Economic Losses Due to Infectious Bursal Disease in Broilers in Mirpur and Kotli Districts of Kashmir - Farooq, M.; Durrani, F.R.; Imran, N.; Durrani, Z.; Chand, N. (International Journal of Poultry Science, 2003)
A systematic investigation was performed on the outbreaks of Infectious Bursal Disease (IBD) using data compiled during the years 1997 and 1998 from 50 broiler farms in Mirpur and Kotli districts. Average mortality due to IBD was 15.31±1.04% with a coefficient of variation of 48.04%. Farms located at various places and vitamin supplementation had no effect on mortality caused by IBD. Season, floor space/broiler, age of the bird, immunization schedule, interval between two batches, presence of coccidiosis in a flock and hygienic status of the farm had a significant effect (p